Osiemnastowieczny Londyn − miasto warte grzechu - Modłasiak, Monika (Acta Universitatis Lodziensis. Folia Historica, 2015)
The eighteenth-century London was a multicultural city, which attracted people from all over the world and all social classes. In the capital of England people tried to find the way to satisfy their desires and make their dreams come true. Due to economic and political changes, the city upon Thames was a great place to settle down. This article is an attempt to answer the questions: why so many people were visiting London and if it was a city worth a sin?